Dexmedetomidine-bupivacaine versus Ketamine-bupivacaine for Ultrasoundguided Axillary Brachial Plexus Block in Forearm and Hand Surgeries: A Tripleblind Randomised Clinical Study - Rohan Jagadish; Nilesh Balaji Giri; Gautami Ramesh Laturkar; Kritika Aggarwal; Saujas Shah (JOURNAL OF CLINICAL AND DIAGNOSTIC RESEARCH, 2026)
Introduction: Single-injection ultrasound-guided axillary brachial plexus block provides effective anaesthesia for forearm and hand surgery, but analgesia is limited by local anaesthetic duration. Dexmedetomidine and ketamine are used as adjuvants, though their comparative axillary-block efficacy remains inadequately defined in clinical studies. Aim: To compare dexmedetomidine and ketamine as adjuvants to bupivacaine for ultrasound-guided axillary block in adult patients undergoing elective forearm and hand surgeries. Materials and Methods: This triple-blind randomised parallelgroup clinical study was conducted in the Department of Anaesthesiology, Krishna Hospital and Medical Centre, Karad, Maharashtra, India. The study included 60 American Society of Anesthesiologists Physical Status (ASA-PS) I-II adults aged more than 18 years undergoing elective forearm and hand surgeries under ultrasound-guided axillary block. Participants were randomised into two equal groups. Group D received 30 mL of 0.25% bupivacaine with dexmedetomidine 100 µg diluted in 2 mL, while Group K received 30 mL of 0.25% bupivacaine with ketamine 100 mg in 2 mL. Sensory and motor onset, sensory, and motor duration, duration of analgesia, rescue analgesic requirement, Visual Analogue Scale (VAS) scores, sedation, satisfaction, haemodynamic variables and adverse events were recorded. Continuous variables were expressed as mean±standard deviation and compared using Student’s unpaired t-test or appropriate parametric tests. Categorical variables were expressed as number and percentage and compared using Chi-square test or Fisher’s exact test. A p-value